A Prospective Observational Study of Significant Airway Events in Intensive Care. (October 2014) - Chillingworth, Simon; Slater, Ben; Simpson, Gavin
This is a single-centre, prospective, observational study that aimed to establish the incidence of airway events and the interventions required to manage these events in a 9-bedded general intensive care unit. During the 30-day study period there were 278 significant airway events requiring 332 interventions. Forty-six (16.5%) events were associated with hypoxia, and medical intervention was required for 25 events (9%) with the remainder managed by trained nurses or physiotherapists. The most frequent events were tube blockage due to secretions (47.8%) and circuit disconnection (14.3%). Events occurred more frequently in those ventilated with tracheostomy compared to endotracheal tube (event rate per ventilator day 1.76 vs 1), but these were less likely to lead to hypoxia (OR 2.93). We have found a rate of airway events of 1.22 per ventilator day and conclude that access to appropriately skilled and trained staff is required to manage these intensive care airway problems.